Survey to Evaluate Escape of Eucalyptus spp. Seedlings from Plantations in Southeastern USA - Mac A. Callaham; John A. Stanturf; William J. Hammond; Donald L. Rockwood; Evelyn S. Wenk; Joseph J. O'Brien (International Journal of Forestry Research)
Interest in biomass-based energy in the southeastern Unites States has led to increased need for fast-growing tree species. Several Eucalyptus species exhibit characteristics that make them attractive in the bioenergy context. However, some of these also possess traits that suggest they could become invasive. To make a preliminary assessment of the risk of seedling establishment in the vicinity of Eucalyptus plantations, we conducted surveys at 3 sites in South Carolina and 16 sites in Florida. In South Carolina, no seedlings were detected in any sample transect. In Florida, we found seedlings within the boundaries of Eucalyptus plantations at 4 of the 16 sites surveyed. We also detected seedlings outside the boundaries of these same four plantations, but only two seedlings were detected at distances >45 m from plantation boundaries. All seedlings from Florida were either E. amplifolia, E. robusta, or E. grandis. The most predictive variable evaluated was latitude, with 27°N being the highest latitude at which seedlings established with regularity. Results of this survey indicate that, under current conditions, the spread of Eucalyptus spp. from plantations should be possible to manage with appropriate monitoring, but this should be evaluated further before Eucalyptus spp. are adopted for widespread planting.